Kegiatan Pemeriksaan Hemoglobin dalam Rangka Skrining Anemia pada Populasi Usia Produktif - Jeffrey Jeffrey; Kurniawan, Junius; Destra, Edwin; Tara, Audina Alianda Dimas (Universitas 17 Agustus 1945 Semarang, 2024)
Anaemia is a common medical condition characterised by a lack of red blood cells or a decrease in haemoglobin levels below normal, which is important for the distribution of oxygen in the body. This disorder has a significant impact on global health, especially in the elderly, pregnant women, and individuals with chronic diseases. Anaemia in women of reproductive age poses a severe health challenge, causing more than 115,000 maternal deaths each year. This activity uses the PDCA (Plan-Do-Check-Act) method to screen for anaemia by measuring haemoglobin and hematocrit levels in the productive age population at PT. Narindo, North Jakarta. The examination results showed that 38 people (28.57%) men and 5 people (3.97%) women had anemia. Routine screening, especially in high-risk populations, is critical for early identification and timely intervention, thereby reducing complications and health care costs. Efficient management through nutritional and pharmacological interventions can improve the quality of life and productivity of individuals suffering from anemia, thereby reducing the wider socio-economic impact.